Klinická symptomatológia a endometriálna histológia pri kontraceptívnych telieskach - Micko, I (Ceskoslovenska gynekologie, 1971)
Even though the mechanism of the antifertile effect of IUDs is not yet completely understood, IUDs create no more complications that other contraceptive methods. The slight increase in secretions from the cervix caused by contact of endometrial tissue with the device and a cell infiltration of the endometrium in this area does not affect the contraceptive effect of the device. No real pathological changes were found. On the contrary, in 5 cases use of the device regularized the cycles of women who had had repeated abortions and very irregular cycles. Expulsion of the device varied according to its size and was corrected by using a larger device.
Keywords: Endometrial Effects; Genitalia, Female; Hemorrhage; Family Planning; Research Methodology; Urogenital System; krvácení; Histocytochemistry; Humans; Genitalia; nitroděložní antikoncepční prostředky; Physiology; Uterus; Time Factors; Iud--side effects; Clinical Research; Contraceptive Methods--side effects; Contraception Termination; Endometrium; Contraception; časové faktory; Intrauterine Devices; ženské pohlaví; histocytochemie; lidé; Biology; Histology; endometrium; Female